Pengaruh Keterlibatan Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan PDAM Sumber Pocong Bangkalan Dengan Motivasi Sebagai Variabel Intervening - Nurul Hidayati; Helmi Buyung Aulia Safrizal (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study discusses about the effect job involvement, job satisfaction, empleyee performance and motivation of PDAM Sumber Pocong Bangkalan. The purposes of this study are to find out the effect job involvement and job satisfaction effect onemployee performance through motivation as an intervening variable. Ita use a quantitative approach population in this study 183 with 65 sample respondents, and used questionnaires in collecting data, using the multiple linear regression and path analyisis, the result showed that : 1) job involvement has a positive and significant effect on motivation. 2) job satisfaction has a positive and significant effect on motivation. 3) job involvement has a positive and significant effect on employee. 4) job satisfaction has a positive and significant effect on employee performance. 5) motivation has a positive and significant effect on employee performance 6) job involvement has a direct effect on employee performance without through the motivation. 7) job satisfaction has a direct effect on employee performance without through the motivation.